PENYEBARAN DAN POTENSI LAHAN GAMBUT DI KABUPATEN BENGKALIS UNTUK PENGEMBANGAN PERTANIAN - Besri Nasrul (Jurnal Agroteknologi, 2010)
In order to develop agriculture in the peatlands, needed data about it's distribution and potency. The study, was done in the in Bengkalis Distric, Riau were conducted in four months. The result of study showed that it’s distribution of tropical peatlands in Bengkalis District was about 82,129.73 ha, differentiated pursuant to land potency: (1) wetland rice is suitable to shallow peats (50- 100 cm); (2) food crop and vegetables is suitable to shallow-middle peats (50-200 cm); (3) fruits is suitable to deep peats (200-300). The crops is suitable in the petlands type, usually also according to shallower peats.